(untitled) (Applied Biological Research, 2014)
An experiment was conducted during winter season of 2007-08 and 2008- 09 at Agricultural Research Station, Morena (MP) on a sandy loam soil to assess the response of mustard (Brassica juncea L.) to varying moisture regime and levels of nitrogen, phosphorus, potash and zinc. Two irrigations applied at flower initiation and siliqua formation stages gave significantly higher growth and yield attributes, water utilization efficiency (WUE), production efficiency, nutrient uptake and oil yield, and resulted in 11.2 and 33.3% higher seed yield over one irrigation applied either at flower initiation- or siliqua-formation-stages, respectively. Among the fertility levels tested, 125% RDF (100, 22, 20.7 and 6.25 kg ha-1of N, P, K and Zn, respectively) gave significantly higher values of growth and yield contributory characters, WUE, production efficiency, nutrient uptake and quality components over 100% RDF (80.0, 17.6, 16.6 and 5.0 kg ha-1of N,P, K and Zn, respectively). Application of 125% RDF gave 19.94, 11.86 and 3.97% higher mustard seed yield over 50, 75 and 100% RDF, respectively. The highest oil content was found in 125% RDF treatment which was significantly superior to 50% RDF. The interaction effect among irrigation and fertility levels was non-significant. Maximum net monitory returns of 40441 and 36916 ha-1and benefit cost ratio of 4.37 and 3.82 were realized under two irrigations and 125% RDF treatments, respectively.